Authorized Course of Instruction for the Quinmester Program. Science The World of Animals, Animal Life, Four Legged and Otherwise. - Dade County Public Schools, Miami, FL.; Dade County Public Schools, Miami, FL. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
This instructional package contains three animal life units developed for the Dade County Florida Quinmester Program. "The World of Animals" is a survey course of the animal kingdom (excluding man) and involves the students in many laboratory investigations and group activities. Typical animals of South Florida and unusual animals of the world are studied. "Animal Life" includes recognition and characteristics of harmful and beneficial animals, natural communities, and energy relationships. "Four Legged and Otherwise" is an elementary course in general zoology with emphasis on the economic value of the fauna of South Florida, ecological relationships, and the effects of pollution. Each booklet includes performance objectives for the unit, lists state-adopted texts, provides a synoptic summary of the course content, suggests activities and projects, indicates audio-visual materials available in the county and from other sources, and recommends reference books. Each booklet contains a chart relating each suggested activity to specific performance objectives. (CP)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Biology; Ecology; Instruction; Objectives; Secondary School Science; Teaching Guides; Units of Study; Quinmester Program